2005
DOI: 10.1002/ps.1140
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of pesticides used on cotton (Gossypium hirsutum) to Trichogramma pretiosum reared on two laboratory‐reared hosts

Abstract: The side-effects of pesticides (insecticides, fungicides, herbicides and plant growth regulators) used on cotton were tested on adults and pupae of Trichogramma pretiosum Riley reared in the laboratory on two different hosts, the Angoumois grain moth (Sitotroga cerealella Olivier) and the Mediterranean flour moth (Ephestia kuehniella (Zeller)). The eggs of the host enclosing the parasitoid pupae received direct pesticide sprays, while the adults of the parasitoid were exposed to the pesticides through contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 24 publications
4
52
0
3
Order By: Relevance
“…O herbicida Gramocil (0,20% paraquat + 0,10% diuron) foi testado por Bastos et al (2005), que ofertaram ovos de A. kuehniella e Sitotroga cerealella (Lepidoptera: Gelechiidae) contaminados ao parasitóide T. pretiosum, resultando em parasitismos de 53,89 e 36,02%, respectivamente, ambos diferindo do tratamento testemunha. Trabalhos envolvendo somente o ingrediente ativo paraquat não foram encontrados na literatura, entretanto se verificou alta mortalidade de adultos de T. pretiosum no presente estudo (Tabela 2, bioensaio III), bem como em pesquisas que envolveram outros ingredientes ativos junto ao paraquat (Bastos et al, 2005).…”
Section: /2006unclassified
See 1 more Smart Citation
“…O herbicida Gramocil (0,20% paraquat + 0,10% diuron) foi testado por Bastos et al (2005), que ofertaram ovos de A. kuehniella e Sitotroga cerealella (Lepidoptera: Gelechiidae) contaminados ao parasitóide T. pretiosum, resultando em parasitismos de 53,89 e 36,02%, respectivamente, ambos diferindo do tratamento testemunha. Trabalhos envolvendo somente o ingrediente ativo paraquat não foram encontrados na literatura, entretanto se verificou alta mortalidade de adultos de T. pretiosum no presente estudo (Tabela 2, bioensaio III), bem como em pesquisas que envolveram outros ingredientes ativos junto ao paraquat (Bastos et al, 2005).…”
Section: /2006unclassified
“…Trabalhos envolvendo somente o ingrediente ativo paraquat não foram encontrados na literatura, entretanto se verificou alta mortalidade de adultos de T. pretiosum no presente estudo (Tabela 2, bioensaio III), bem como em pesquisas que envolveram outros ingredientes ativos junto ao paraquat (Bastos et al, 2005). Na literatura não foram encontrados trabalhos relacionados à seletividade de herbicidas a Trichogramma para a cultura do milho, pois somente alguns inseticidas foram testados até o momento (Cruz, 1995;Pratissoli et al, 2004).…”
Section: /2006unclassified
“…Pests and their natural enemies are generally from different orders. Moreover, insect growth regulators affect immature stages of insects during the whole molting process (Reynolds 1987), and, thus, adults of non-target species, such as parasitoids and predators, are rarely affected (Bastos et al 2006). Lufenuron, triflumuron and novaluron, belonging to the Benzoylurea chemical group, as well as diflubenzuron, were also described as harmless to T. pretiosum (Carvalho et al 2010) be recommended for integrated pest management programs.…”
Section: Resultsmentioning
confidence: 99%
“…The neonicotinoids Thiacloprid and acetamiprid demonstrated strong larvicidal and ovicidal activity but were somewhat weaker adulticides than the conventional broad-spectrum compounds while, Azinphosmethyl, phosmet, indoxacarb, Thiacloprid, and acetamiprid were all toxic to the egg parasitoid T. minutum Riley. Also, [14] found that Thiacloprid did not affect T. pretiosum emergence when eggs of S. cerealella enclosing pupae of the wasps were surface treated.…”
Section: Residue Toxicity On Parasitoid Adultsmentioning
confidence: 95%
“…In a standard IOBC glass plate assay, residues of Thiacloprid (SC 480) severely affected adult stages of the cereal aphid parasitoid Aphidius rhopalosiphi whereas pre-imaginal stages (which develop within the host) revealed a high tolerance against spray treatment with the same insecticide [13]. Also [14] studied the selectivity of pesticides including Thiacloprid on cotton Gossypium hirsutum to T. pretiosum relared on two laboratory-reared hosts.…”
Section: Introductionmentioning
confidence: 99%